ANALISIS PERBEDAAN PENDAPATAN SISTEM JAJAR LEGOWO 2:1 DAN 4:1 PADA USAHATANI PADI SAWAH (ORYZA SATIVA L.) DI KELURAHAN KULAHI KECAMATAN WAWOTOBI KABUPATEN KONAWE - Sukratman, I Made (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Analysis of the Difference in Income of 2: 1 and 4: 1 Jajar Legowo Systems in Rice Field (Oryza sativa L.) Farming in Kulahi Village, Wawotobi District, Konawe Regency. The objectives of this research are: 1. To find out the income of lowland rice farmers who use 2:1 jajar legowo planting system and 4: 1 jajar legowo in Kulahi Village, Wawotobi District, Konawe District. 2. Knowing income differences in the use of 2:1 jajar legowo planting system and jajar legowo 4: 1 lowland rice farming in Kulahi Village, Wawotobi District, Konawe District. This research was conducted in May to July 2018, in Kulahi Village, Wawotobi District, Konawe District. Determination of this location was carried out intentionally (purposive) with the consideration that the area most of the farmers planted rice paddy field system jajar legowo The results showed that: 1. Jajar legowo 2:1 planting system could increase productivity by 5,650 Kg/Ha with income of Rp. 2,344,281,-/Ha while using a 4:1 jajar legowo planting system yielded a productivity of 5,728Kg / Ha with income of Rp.2,704,091,-/Ha. 2. The results of productivity analysis using the 4:1 jajar legowo planting system (5.728Kg/Ha) are higher than the productivity in the 2: 1 legowo jahan planting system (5.650Kg/Ha); while the income in the jajar legowo 4: 1 planting system (Rp.2,704,091/Ha) is higher than the income in the non-row cropping system (Rp.2,344,281/Ha). the results of the average difference test above shows that Thitung> T table (1.17> 2.0) which means that H0 is rejected and H1 is accepted. Thus at Î± = 0.05 the income in the 4: 1 jajar legowo planting system is greater than the income in the legowo 2: 1 planting system.